Reclamation and commercialization of post-mined sites through palm oil plantations in Ghana: a financial feasibility assessment report - Atampugre, Gerald; Ametefe, D. L.; Tilahun, Seifu A. (International Water Management Institute, 2025)
The reclamation of post-mined land commissioned under the Inclusive Landscape Management Plan (ILMP) by the International Water Management Institute (IWMI) is a strategically important initiative to convert degraded mining landscapes into productive agricultural land. The approach combines oil palm cultivation with carefully selected leguminous crops to restore soil fertility and deliver sustainable socio-economic and environmental outcomes—the triple bottom line. Building on a successful pilot in the Ahafo Ano Southwest District, the initiative was initially framed through an Investment Memorandum (IM) as a scalable, investor-ready opportunity. The original model proposed private investment to finance the high-risk reclamation phase in return for long-term land access, supported by a 70:30 profit-sharing arrangement favoring investors while ensuring meaningful benefits for local communities.